Inorganic nutrients and dissolved oxygen in the Canary Current Large Marine Ecosystem - Pelegrí, Josep Lluís; Peña-Izquierdo, Jesús (Instituto Español de Oceanografía, 2015)
10 pages, 6 figures Inorganic nutrients increase with depth as a result of the enhanced remineralization of organic matter with aging waters (the time since they were last near the sea surface), and the opposite happens with dissolved oxygen (except within the saturated surface mixed layer). In the Canary Current Large Marine Ecosystem there is also a marked latitudinal gradient, with the Cape Verde Front separating relatively nutrient‐poor and oxygen‐rich subtropical waters from the nutrient‐rich and oxygen‐poor tropical waters. Along a latitudinal band off North‐West Africa, coastal upwelling brings the subsurface waters towards the sea surface, locally raising the inorganic nutrient levels. This becomes an important lateral source to both gyre especially to the nutrient‐poor subtropical one, taking place through lateral mixing (mainly as a result of the instability of the coastal‐upwelling baroclinic jet) and localized coastal filaments (in those regions, typically capes, where the coastal flow converges and offshore advection takes place). In the southernmost portion of our domain, within tropical waters, there is also high (wind‐induced) offshore primary production. This, together with the slow ventilation of the subsurface waters, leads to much enhanced remineralization, producing a region with very low oxygen and high inorganic nutrient levels, the oxygen minimum zone of the North Atlantic Ocean This review has been supported by projects CANOA (CTM2005-00444/MAR), MOC2 (CTM2008-06438-C02-01) and TIC-MOC (CTM2011–28867), funded by the Spanish government. Jesús Peña-Izquierdo was funded by the Spanish government, through a FPI doctoral grant linked to project MOC2 Peer Reviewed